SLANG LANGUANGES OF GEN ALPHA ON TIKTOK VIDEOS: HUMANITIES LEARNING IN THE DIGITAL ERA - Fajar, Abdurrahman Malik; Mentari, Putri (Journal of Intensive Studies on Language, Literature, Art, and Culture, 2025)
This study examines slang language use among Generation Alpha in Indonesia, focusing on TikTok videos from the Monella and Marsonn Family accounts. Using a qualitative descriptive approach and sociolinguistic analysis, it explores language variations, their functions, and influencing factors. Findings indicate that slang reflects bilingual identity (English-Indonesian) and is shaped by informal speech settings, age, and speaker intent. The research highlights how digital platforms contribute to evolving linguistic trends among younger generations.